Cell wall ingrowths in nematode induced syncytia require UGD2 and UGD3. - Shahid Siddique; Miroslaw Sobczak; Raimund Tenhaken; Florian M W Grundler; Holger Bohlmann (PLoS ONE)
The cyst nematode Heterodera schachtii infects roots of Arabidopsis plants and establishes feeding sites called syncytia, which are the only nutrient source for nematodes. Development of syncytia is accompanied by changes in cell wall structures including the development of cell wall ingrowths. UDP-glucuronic acid is a precursor of several cell wall polysaccharides and can be produced by UDP-glucose dehydrogenase through oxidation of UDP-glucose. Four genes in Arabidopsis encode this enzyme. Promoter::GUS analysis revealed that UGD2 and UGD3 were expressed in syncytia as early as 1 dpi while expression of UGD1 and UGD4 could only be detected starting at 2 dpi. Infection assays showed no differences between Δugd1 and Δugd4 single mutants and wild type plants concerning numbers of males and females and the size of syncytia and cysts. On single mutants of Δugd2 and Δugd3, however, less and smaller females, and smaller syncytia formed compared to wild type plants. The double mutant ΔΔugd23 had a stronger effect than the single mutants. These data indicate that UGD2 and UGD3 but not UGD1 and UGD4 are important for syncytium development. We therefore studied the ultrastructure of syncytia in the ΔΔugd23 double mutant. Syncytia contained an electron translucent cytoplasm with degenerated cellular organelles and numerous small vacuoles instead of the dense cytoplasm as in syncytia developing in wild type roots. Typical cell wall ingrowths were missing in the ΔΔugd23 double mutant. Therefore we conclude that UGD2 and UGD3 are needed for the production of cell wall ingrowths in syncytia and that their lack leads to a reduced host suitability for H. schachtii resulting in smaller syncytia, lower number of developing nematodes, and smaller females.